Cryptic Kultarr: Integrative Taxonomy Reveals Unrecognized Species of Carnivorous Marsupial (Dasyuridae: Antechinomys) in Arid Australia - Cameron S. Dodd; Renee A. Catullo; Kenny J. Travouillon; Andrew M. Baker; Michael Westerman; Linette S. Umbrello (Ecology and Evolution, 2025)
ABSTRACT Globally, mammal species are experiencing unprecedented rates of extinction. Despite this, many small mammals remain understudied and even undescribed, posing a major barrier to effective conservation planning. Without formal study and documentation, it is impossible to make well‐informed management decisions for these species. This issue is particularly pronounced in Australia, where not only is the mammal extinction rate the highest in the world, but the vast inaccessibility of much of the continent, combined with a shortage of expert taxonomists, has left a large portion of small mammal diversity poorly documented. One example of this is the kultarr (Antechinomys laniger), a small, insectivorous marsupial in the family Dasyuridae that is distributed across much of the Australian arid zone. While currently considered a single species, previous morphological and molecular studies have suggested the presence of cryptic taxa within the group. Here, we resolve the taxonomy of the kultarr using 12S mitochondrial sequence data and genome‐wide single nucleotide polymorphisms. We identify three clades of kultarr that are morphologically distinct, largely allopatric, and show minimal evidence of genetic admixture. These clades differ in hindfoot length, body size, ear size, and craniodental morphology. The clades consist of an eastern semi‐arid clade, a central Channel Country/Kati Thanda‐Lake Eyre Basin clade, and a western deserts clade. We rediagnose A. laniger sensu stricto as the eastern clade, resurrect A. spenceri as the central clade, and describe a new species, A. auritus sp. nov., as the western clade. This research highlights the importance of integrating morphological and genetic data in small mammal taxonomy and emphasizes the need for comprehensive geographic sampling within widespread species complexes.